2009
DOI: 10.4314/ari.v5i1.48720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition on the red blood cells of Trypanosome-infected female rats

Abstract: Trypanosomiasis is of great interest to farmers in Sub-Saharan Africa. It is a disease that retards agricultural development in general and needs urgent atten ion. It has been noted that it causes aneamia in its host which often may lead to death. Many researches showed that dietary supplement can enhance trypanotolerance in various hosts. Diet is important in modulating the severity of its pathophysiological ef ects and can also influence the rate of recovery. Using a control diet (Diet 1)) was only chicks' m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The diets having different components of egg such as egg white, ovalbumin, and egg yolk with the same nitrogen contents showed a nonsignificant (p ≤ .05) effect on RBCs at the end of 42-day trial of rats (Kobayashi et al, 2015). Contrary results were found by Ufele et al (2008), and RBCs in mice with different levels of plant protein diets (soybean and corn meal) were higher and significantly (p ≤ .05) different. In another research, children fed animal protein-based lunch had higher RBCs than those fed the vegetable protein-based lunch.…”
Section: F I G U R E 1 Collection Of Blood Samples From Pups' Jugular...mentioning
confidence: 77%
“…The diets having different components of egg such as egg white, ovalbumin, and egg yolk with the same nitrogen contents showed a nonsignificant (p ≤ .05) effect on RBCs at the end of 42-day trial of rats (Kobayashi et al, 2015). Contrary results were found by Ufele et al (2008), and RBCs in mice with different levels of plant protein diets (soybean and corn meal) were higher and significantly (p ≤ .05) different. In another research, children fed animal protein-based lunch had higher RBCs than those fed the vegetable protein-based lunch.…”
Section: F I G U R E 1 Collection Of Blood Samples From Pups' Jugular...mentioning
confidence: 77%
“…Due to the different morphological structures and shape of RBCs, they play an important role in transporting oxygen and nutrients to all parts of the body ( Barbalato and Pillarisetty, 2020 ). Ufele et al (2008 ) found positive variations in RBC levels in mice that fed on plant-based protein (soybean and corn meal). Similarly, higher RBCs were found due to the bioavailability of animal protein than plant-based protein ( Aguirre et al, 1959 ).…”
Section: Discussionmentioning
confidence: 99%